2005
DOI: 10.5713/ajas.2006.286
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Change in Meat Quality Parameters on Pig Longissimus dorsi Muscle by the Addition of Fermented Persimmon Shell Diet

Abstract: The objective of the present study was to investigate the effects of growth performance, chemical composition and meat quality parameters by the addition of fermented persimmon shell diets (FPSD). The experimental animals were ninety-six Berkshires. The pigs were allotted at 8 per pen in front-open building with three replicate pens per treatment. Until 61±1 kg live weight at 140 days, the animals were fed growing diet, after which, experimental samples were fixed at 0, 3, 5 and 7% FPSD as C, T1, T2 and T3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…Some studies have reported that crude fat in meat decreased with an increase in crude protein (Shields et al, 1983). Kim et al (2006a) reported that chemical composition of meat was affected by the addition of fermented diet. Our study indicates that addition of up to 5% of FOMP decreased carcass weight and dressing, and increased backfat thickness when compared with C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that crude fat in meat decreased with an increase in crude protein (Shields et al, 1983). Kim et al (2006a) reported that chemical composition of meat was affected by the addition of fermented diet. Our study indicates that addition of up to 5% of FOMP decreased carcass weight and dressing, and increased backfat thickness when compared with C.…”
Section: Resultsmentioning
confidence: 99%
“…Rosenvold et al (2002) reported that pH and meat colour were affected by diet ingredients. Kim et al (2006a) reported that meat quality characteristics, meat and backfat colour were affected by the addition of fermented diet. Our research indicates that meat quality characteristics, meat and backfat colour in meat were changed by the addition of FOMP in finishing Berkshire.…”
Section: Resultsmentioning
confidence: 99%
“…2002). The supplemental 7% fermented persimmon shell diet decreased moisture concentration and increased CF concentration of the Longissimus doris in Berkshire pigs (Kim et al . 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, stock farms including pig farms are developing fermented diets for the production of high‐quality meat, and some diets have already been developed and are being applied to stock farming (Kim et al . 2001, 2006a,b; Song 2001; Park et al .…”
Section: Introductionmentioning
confidence: 99%